Familial non-cystic fibrosis mucus inspissation of respiratory tract. Issue 9 (September 1975) - Perlman, M; Williams, J; Hirsch, M; Bar-Ziv, J
Abstract : Perlman, M., Williams, J., Hirsch, M., and Bar-Ziv, J. (1975). Archives of Disease in Childhood, 50, 727. Familial non-cystic fibrosis mucus inspissation of respiratory tract. Two sibs, whose parents are first cousins, have had chronic obstructive airways disease from birth with recurrent otitis media, sinusitis, and mastoiditis. The disease, associated with clinically abnormal mucus, differs from other familial obstructive airways diseases and probably constitutes a new entity.